An IoT-based energy-management platform for industrial facilities. (15th February 2016) - Wei, Min; Hong, Seung Ho; Alam, Musharraf
Highlights: Facility energy management systems require interconnection and interoperation. An IoT-based communication framework with a common information model is proposed. A practical example of an IoT-based energy-management platform. Validation of the ability of the platform to enhance system interoperability. The platform with improved energy management achieves energy saving targets. Abstract: Interconnectivity and interoperability are very important features in the development of integrated energy management systems for industrial facilities. A simple and common strategy for exchanging energy-related information among the entities in a facility is currently lacking. To this end, the purpose of this study is to present an IoT-based communication framework with a common information model to facilitate the development of a demand response (DR) energy management system for industrial customers. Additionally, we developed and implemented an IoT-based energy-management platform based on a common information model and open communication protocols, which takes advantage of integrated energy supply networks to deploy DR energy management in an industrial facility. The experimental results of this study demonstrate that the proposed platform can not only improve the interconnectivity of the entities in industrial energy management systems but also reduce the energy costs of industrial facilities.